The equilibrium time and deformation characteristic of sulfate saline soil in 1D saline expansion test - Li К.; Ji, Y. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The salt expansion disease is serious for the soil containing sodium sulfate in cold regions. This paper carried out one-dimensional swelling tests of saline soil, and numerical cooling tests of soil to explore the stability time of salt swelling deformation and determine the standard procedure of the salt swelling test method. The test results demonstrate that: (A) the temperature equilibrium and crystallization process are almost completed simultaneously in the one-dimensional (1D) salt expansion test; (B) Referring to the standard of consolidation test, a standard that the expansion rate is less than 0.02mm/h can be used in the salt expansion test; (C) The required time for temperature equilibrium of soil is quadratic to sample size and is much faster with liquid bath condition comparing to gas bath condition. Because the deformation and temperature are synchronized, the deformation stabilization time of different size samples in different cooling media is recommended.This can provide a reference for the deformation equilibrium time of the salt swelling test.